Incidence of persistent and high-risk human papillomavirus infection and associated factors among HIV-positive women in China, 2015-2016 - Yaping Qiao; Ailing Wang; Liwen Fang; Linhong Wang (BMJ Publishing Group, 2021)
Background: Persistent human papillomavirus (HPV) infection is the necessary factor for cervical cancer. Human immunodeficiency virus (HIV)-positive women are a high-risk population for cervical cancer, but little is known about persistent HPV infection among HIV-positive women in China. We aimed to investigate the persistence and incidence of infection with high-risk HPV (hrHPV) and associated factors among HIV-positive women in China. Method: Using a prospective observational study design, we collected data from 670 HIV-positive women in five counties of three provinces through interviews, medical record reviews, health examination, and laboratory tests at a baseline survey in 2015 and a follow-up survey in 2016. We tested HIV-positive women for hrHPV infection using the Cobas 4800 HPV test, and analyzed factors associated with persistence and new incidence of hrHPV infection using logistic regression. Results: After an average of 15 months at follow-up, the persistence and new incidence rates of hrHPV infection were 38.0% (46/121, 95% CI: 29.2%-46.8%) and 8.3% (35/420,95% CI: 5.7%-11.1%), respectively. HIV-positive women in Yunnan and Guangxi were more likely to have persistent hrHPV infections than those in Xinjiang (aOR = 3.18, 95% CI: 1.00-10.14, p = 0.05; aOR = 6.38, 95% CI: 2.29-17.77, p < 0.001). Migrant women had a higher rate of new hrHPV incidence than local women (aOR = 4.48, 95% CI: 1.65-12.15, p = 0.003). HIV-positive women from Xinjiang were 6.5 times more likely to be newly infected with hrHPV than those from Yunnan (95% CI: 2.40-17.60, p < 0.001). HIV-positive women with HBV infection had a higher risk of being infected with hrHPV than those without HBV infection (aOR = 3.48, 95% CI: 1.13-10.71, p = 0.029). Conclusions: The persistence and new incidence rates of hrHPV infection among HIV-positive women were high and varied significantly between regions. HBV infection and being among the migrant population were associated with new hrHPV infection.